Adsorptive Cathodic Stripping Voltammertries Of Lead In Water Samples Using 2, 2'-Bipyridyl; 1,10- Phenanthroline And Nitrite Ions - Jawad, Masar Hadi (2013)
A new differential pulse adsorptive cathodic stripping voltammetric (DPAdCSV) method was developed for the determination of lead concentration in aqueous solution.. This was based on complexation of lead with combination of two complexing agents viz 2,21-hipyridyl and 1,1 O-phenanthroline with nitrite at hanging mercury drop electrode (HMDE). Variables affecting the response such as pH, supporting electrolyte, initial purge time, drop size, stirring speed, deposition potential, deposition and equilibration times, sweep rate, pulse amplitude and ligand concentration were investigated. Using the first reagent 2,2'-bipyridyl with nitrite[reagent (I)] and under optimized conditions the relationship between peak current and lead concentration was linear in the range of 10-500 ng mL-l. The limit of detection was found to be 0.48 ng mL-l. The relative standard deviation (RSD) for n= 9 determinations of standard 25 ng mL-I Pb2+ was to 1.74% with linear regression coefficient (R2) 0.9991.